Presence of Xylella fastidiosa in sweet orange fruit and seeds and its transmission to seedlings - Li, W. B.; Pria, W. D. [UNESP]; Lacava, P. M.; Qin, X.; Hartung, J. S. (Scientific Societies, 2003)
Xylella fastidiosa, a xylem-limited bacterium, causes several economically important diseases in North, Central, and South America. These diseases are transmitted by sharpshooter insects, contaminated budwood, and natural root-grafts. X. fastidiosa extensively colonizes the xylem vessels of susceptible plants. Citrus fruit have a well-developed vascular system, which is continuous with the vascular system of the plant. Citrus seeds develop very prominent vascular bundles, which are attached through ovular and seed bundles to the xylem system of the fruit. Sweet orange (Citrus sinensis) fruit of cvs. Pera, Natal, and Valencia with characteristic symptoms of citrus variegated chlorosis disease were collected for analysis. X. fastidiosa was detected by polymerase chain reaction (PCR) in all main fruit vascular bundles, as well as in the seed and in dissected seed parts. No visual abnormalities were observed in seeds infected with the bacterium. However, the embryos of the infected seeds weighed 25% less than those of healthy seeds, and their germination rate was lower than uninfected seeds. There were about 2,500 cells of X. fastidiosa per infected seed of sweet orange, as quantified using real-time PCR techniques. The identification of X. fastidiosa in the infected seeds was confirmed by cloning and sequencing the specific amplification product, obtained by standard PCR with specific primers. X. fastidiosa was also detected in and recovered from seedlings by isolation in vitro. Our results show that X. fastidiosa can infect and colonize fruit tissues including the seed. We also have shown that X. fastidiosa can be transmitted from seeds to seedlings of sweet orange. To our knowledge, this is the first report of the presence of X. fastidiosa in seeds and its transmission to seedlings.
Keywords: Bacteria (microorganisms); Citrus; Citrus sinensis; Hexapoda; Insecta; Pera; Valencia; Xylella fastidiosa